2010
DOI: 10.1063/1.3293176
|View full text |Cite
|
Sign up to set email alerts
|

Routes to complex dynamics in a ring of unidirectionally coupled systems

Abstract: We study the dynamics of a ring of unidirectionally coupled autonomous Duffing oscillators. Starting from a situation where the individual oscillator without coupling has only trivial equilibrium dynamics, the coupling induces complicated transitions to periodic, quasiperiodic, chaotic, and hyperchaotic behavior. We study these transitions in detail for small and large numbers of oscillators. Particular attention is paid to the role of unstable periodic solutions for the appearance of chaotic rotating waves, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 63 publications
1
67
0
9
Order By: Relevance
“…Zheng et al [12] already in 1998 pointed out that the behavior of the order parameter "indicates the coexistence of multiple attractors of phase locking states" above the synchronization critical coupling, K s . Even when synchronization with coexistence of attractors has been reported by different authors and in different fields below K s [12][13][14][20][21][22][23][24][25], nobody, to the best of our knowledge, has pursued the matter above full synchronization. If we have the intention to simulate real systems, mostly in technological applications, it is important to know whether we can move freely below and also above synchronization within stable solutions and to know whether they are unique.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [12] already in 1998 pointed out that the behavior of the order parameter "indicates the coexistence of multiple attractors of phase locking states" above the synchronization critical coupling, K s . Even when synchronization with coexistence of attractors has been reported by different authors and in different fields below K s [12][13][14][20][21][22][23][24][25], nobody, to the best of our knowledge, has pursued the matter above full synchronization. If we have the intention to simulate real systems, mostly in technological applications, it is important to know whether we can move freely below and also above synchronization within stable solutions and to know whether they are unique.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown, that increasing the coupling strength leads to selfoscillation birth [2,3]. Hence, the system which is investigated in our paper, represents a special type of generator under external force.…”
Section: Introductionmentioning
confidence: 99%
“…Oscillator chains can be divided into two groups: self-excited, which demonstrate stable limit cycle without external driving [1][2][3][4][5] and strictly dissipative chains, which have stable steady state without forcing [6][7][8][9]. For the ring of unidirectionally coupled Duffing oscillators [2] and for the ring of unidirectionally coupled Toda oscillators with nonlinear coupling function [3], it has been shown that with the increase of coupling coefficient the stable fixed point undergoes Andronov-Hopf bifurcation where the stable limit cycle may appear [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such as drive-response or activepassive of the system, direct bi-directional (mutual) coupling or unidirectional (master-slave) diffusive coupling between the oscillators [14][15][16]. In this connection we introduce a linear feedback coupling [17] of the individual system and coupled mutually of the two systems. For a particular choice of parameter, we confirm the existence of the anticipatory synchronization via phase synchronization the coupling co-efficient is varied.…”
Section: Introductionmentioning
confidence: 99%